The impact of environmental contaminants, air pollution, and social deprivation on childhood leukemia survival in California - Hernandez, Fernando; Stewart, Eric; Morimoto, Libby M; Kang, Alice Y; Winestone, Lena E; Metayer, Catherine (Frontiers in Oncology, 2025)
IntroductionDespite advances in leukemia treatment, disadvantaged children experience worse outcomes. We evaluated the impact of intertwined socioeconomic and pollution burdens on childhood leukemia survival, focusing on ambient air pollution, a known carcinogen.MethodsParticipant data were obtained from the California Childhood Leukemia Study (1995-2015) and linked by diagnosis residence to the CalEnviroScreen (CES) 3.0 database, that characterizes neighborhood pollution burden and area-based population vulnerabilities across California. Five-year survival analyses were performed using Kaplan-Meier estimators and Cox proportional hazards ratio (HR) models with 95% confidence intervals (CI), adjusting for individual socio-demographic and clinical prognostic factors.Results124 out of 1,210 children with acute lymphoblastic leukemia (ALL) died within 5 years of diagnosis. Living in an area with a medium/high CES composite score for both pollution and population/social burdens was associated with decreased ALL survival, compared to a low CES score (HR = 2.19; 95% CI: 1.19-3.91), with population/social burden driving this observation (HR = 1.85; 95% CI: 1.06-3.21). HRs for medium/high composite, particulate matter (PM2.5), and ozone scores were the highest among children with ALL molecular subtypes known to have unfavorable prognosis (i.e., high-hyperdiploidy negative, CDKN2A and IKZF1 deletions). For acute myeloid leukemia (AML) (49 deaths among 178 cases), living in an area with medium/high score for population/social burden was associated with an increased risk of death (HR = 2.21; 95% CI: 0.99-4.94).ConclusionHigh cumulative community burden, especially social deprivation, was associated with reduced survival of childhood ALL and AML, while high levels of PM2.5 and ozone were associated with reduced survival in specific ALL subtypes.